The Effectiveness of Group Work Methods on Students' Independence in Learning Integrated Science - Saputri, Aryani; Hetilaniar; Dina Sri Nindiati (Journal of Practice Learning and Educational Development, 2025)
Research This research is motivated by the lack of learning independence during the learning process at SDN 36 Palembang. The purpose of this study is to determine the influence of group work methods on the independence of learning science in class II students of SDN 36 Palembang. The research method used in this study is quantitative using the Pre-experiment method. The sample in this study was class IIA as many as 22 students. The data collection techniques used were questionnaires, tests, and documentation. The analysis in this study used the t-test. The t-test data results show that the sig. (2-tailed) value is 0.000 <0.05. Which means Ho is rejected and Ha is accepted. This means that there is a significant difference between the results of student learning independence in the pretest and posttest data. Thus, the effectiveness of the group work method on the independence of learning science in class II students of SDN 36 Palembang is recorded.